2006
DOI: 10.1590/s1415-54192006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação comparativa dos efeitos maxilares da expansão rápida da maxila com os aparelhos de Haas e Hyrax

Abstract: Objetivo: avaliar cefalometricamente os efeitos da expansão rápida da sutura palatina mediana sobre o posicionamento vertical e sagital da maxila, comparando os aparelhos de Haas e Hyrax. Metodologia: a amostra consistiu de 93 telerradiografias obtidas de 31 pacientes jovens, brasileiros, de ambos os gêneros, na faixa etária inicial média de 13 anos e 2 meses. As radiografias foram tomadas ao início do tratamento (pré-disjunção), imediatamente após a disjunção (pós-disjunção) e ao final do nivelamento. Resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
(41 reference statements)
0
4
0
4
Order By: Relevance
“…3,8 The Hyrax expansor are better hygienic and indicated for SARME, while the Haas have better distribution of forces because they have an acrylic covering that rests on the palate. 11 Both NSARME and SARME improve upper airflow, decreasing respiratory distress, since they promote the increase of the air cavity. 1,9 There is no significant improvement in the results of the expansion when the osteotomy of the pterygoid pillar is performed.…”
Section: Table 1 Major Consideration On the Sarme And Nsarmementioning
confidence: 99%
See 1 more Smart Citation
“…3,8 The Hyrax expansor are better hygienic and indicated for SARME, while the Haas have better distribution of forces because they have an acrylic covering that rests on the palate. 11 Both NSARME and SARME improve upper airflow, decreasing respiratory distress, since they promote the increase of the air cavity. 1,9 There is no significant improvement in the results of the expansion when the osteotomy of the pterygoid pillar is performed.…”
Section: Table 1 Major Consideration On the Sarme And Nsarmementioning
confidence: 99%
“…The areas of bone resistance in the jaw are palatine suture, frontal suture, zygomatic-temporal suture, intermaxillary suture and, mainly, the pterygoid process, where some surgeons opt for separation, since the risk of damage to the pterygoid plexus is large. 3 In a comparative study with 31 randomly divided patients, where the Group used the Hyrax expander and Group B the Haas expander, Scanavini et al, 11 found that Hyrax expanders demonstrated a higher risk of relapse. In the sequence, Claro et al, 12 found significant changes in intercanal and intermolar distances using the Hyrax orthodontic appliance, thus proving a greater posterior cross-sectional increase.…”
Section: Table 1 Major Consideration On the Sarme And Nsarmementioning
confidence: 99%
“…The main goal is maxillary disjunction by palatal expanders, in order to improve the transversal dimension of patients affected by maxillary deficiencies (6,7) . Disjunction may be performed by fixed orthodontic expanders, like Haas, which is a tooth-tissue-borne device, Hyrax and McNamara Expander, which are classified as tooth-borne (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Expanders have an expanding screw, located parallel to the midpalatal suture, activated so that it accumulates a significant quantity of forces, in order to break the resistance offered by such suture and by the pterygopalatine, frontal maxillary, nasal maxillary and zygomaticomaxillary ones (8) . RME may also bring positive results to the oral and nasopharynx anatomy, as well as beneficial effects to hearing (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Lehman Jr. e Haas (1990), em adultos, a expansão rápida palatina é freqüentemente associada às falhas, como inclinação lateral dos dentes e do osso alveolar, inabilidade para distração da sutura média palatina, necrose da mucosa pelo aparelho expansor e recidiva. Além disso, deficiência unilateral verdadeira não pode ser efetivamente tratada com expansão maxilar rápida convencional porque os efeitos são sempre bilaterais (Chung et al, 2001;Scanavini et al, 2006;Melo et al, 2006).…”
Section: Referencesunclassified